Training on making wreaths for disability - Siregar, Hairani; Ginting, Bengkel (Talenta Publisher, 2019)
This Community Service Program is one of the efforts made so that people with disabilities can be economically independent by providing skills training. The skills training provided is a skill that is tailored to the interests and types of disability. One type of skills provided is training in making bouquets. Flower wreath making services at this time, especially in big cities like Medan City are needed. The results of this training the participants were able to make a bouquet of flowers according to the trainer's team. This training makes the disabilities as trainees have economic resources for survival both as family members and family heads.